Mitigation and Emergency Management System of Landslide in Ponorogo District, Indonesia - Arif Basofi; Arna Fariza; Imam Mustafa Kamal (JOIV : International Journal on Informatics Visualization, 2019)
Ponorogo district, in East Java Province, is one area that is often hit by landslides. In addition to threatening the safety of residents, this landslide caused dozens of houses and public infrastructure to be damaged. The losses caused by this landslide disaster also reached billions of rupiah each year. Integrated of emergency mitigation and response systems for landslides are needed to provide information accurately and widely to the community. This paper proposes a new framework of mitigation and emergency system for landslide in Ponorogo district. The system can analyze, display, explore and store vulnerability data based on web GIS application. The information generated from the mitigation system is a landslide susceptibility map using the analytical hierarchy process (AHP) - Natural break method. The landslide susceptibility index is produced based on 4 factors that cause landslides including slope, soil type, land use and rainfall. The map displays 4 levels of vulnerability including very low, low, moderate and high. The mitigation system is equipped with information features for the community about handling landslides. Pearson's Chi-squared test showed the classification class of vulnerability was declared very significant result. Emergency system information in the form of alternative route information and nearest evacuation sites.